2016
DOI: 10.1111/ssqu.12343
|View full text |Cite
|
Sign up to set email alerts
|

Eyes Wide Shut: Democratic Reversals, Scientific Closure, and the Study of Politics in Eurasia*

Abstract: Objectives The article examines the relationship between democratic reversals and scientific closure. It focuses on the effects that authoritarian and hybrid regimes are likely to have on the ways scholars study them and conduct their fieldwork. Method Thematic content analysis of articles on Eurasian politics published over a 10‐year period, with particular attention paid to reported methods and fieldwork. Results Scientific closure had as much to do with research cycles in the discipline as with democratic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…A more recent study on the political risks of field research in Central Asia found that '(s)everal respondents reported that they no longer work in Uzbekistan' and a 'few respondents singled out Turkmenistan and Azerbaijan as sites where they have experienced significant censorship/restrictions, chosen not to go, or experienced difficulty going' (CESS 2016, 7). Goode (2010) initially discerned a relation between Russia becoming more autocratic and a decline in fieldwork, but qualified his conclusions in a later study of the broader region (Goode 2016). Nonetheless, we would logically expect the most repressive regimes within the authoritarian universe to be less likely settings for field research: either because it would be too dangerous, or simply because it is impossible to gain access.…”
Section: Constrained Choicesmentioning
confidence: 93%
See 1 more Smart Citation
“…A more recent study on the political risks of field research in Central Asia found that '(s)everal respondents reported that they no longer work in Uzbekistan' and a 'few respondents singled out Turkmenistan and Azerbaijan as sites where they have experienced significant censorship/restrictions, chosen not to go, or experienced difficulty going' (CESS 2016, 7). Goode (2010) initially discerned a relation between Russia becoming more autocratic and a decline in fieldwork, but qualified his conclusions in a later study of the broader region (Goode 2016). Nonetheless, we would logically expect the most repressive regimes within the authoritarian universe to be less likely settings for field research: either because it would be too dangerous, or simply because it is impossible to gain access.…”
Section: Constrained Choicesmentioning
confidence: 93%
“…Naivety is a commonly used interview strategy (Goode 2011;Solinger 2006;HenrionDouncy 2013), typically more available to young women and foreigners. Our China researcher, while not actually foreign, uses both elements, especially with older men in senior positions (whether in government, research institutions, or companies) who often possess both stereotypical views of young women and valuable information.…”
Section: Work With What You Havementioning
confidence: 99%
“…Goode's article similarly considers the relationship between regime change and scholarship, focusing on studies of post‐Soviet politics before and after the wave of Color Revolutions in the 2000s (Goode, ). While the scientific opening of the 1990s and the booming study of postcommunist democratization generated a wealth of data and connected post‐Soviet politics with broader theoretical studies in comparative politics, these sit uneasily with the retreat from democracy across Eurasia.…”
Section: The Qualitative Inductive Cornerstone In the Study Of Authomentioning
confidence: 99%
“…Such restrictions, created by the situation on the ground as well as the preferences of the home institution, infl uence the themes and types of research fi ndings that emerge from a particular country (Reny 2011). The lack of previously established infrastructure and the limited availability of secondary literature and ongoing academic debate can also lead researchers to focus on more "established" research areas (Goode 2011). In the case of Myanmar, I would argue that the situation of migrants and refugees in Thailand and elsewhere (although certainly worth the att ention) has featured disproportionally in academic research.…”
Section: Balancing the Risks And Benefi Ts Of Researchmentioning
confidence: 99%